Mystery and contingency in correctional education - G. Walker (Journal of Prison Education and Reentry, 2016)
Citing the work of Maxine Greene, Maurice Merleau-Ponty, and Thom Gehring, this paper makes the argument that correctional educators should attempt to accept that they will never fully understand the lives and perspectives of their students. Noting that some of the questions correctional educators have about the lived experiences of incarcerated and formerly incarcerated students cannot be answered in a way that is fully comprehensible to those who have not lived as prisoners, the paper suggests that developing comfort with mystery will allow educators to focus on instruction.